2022
DOI: 10.1038/s41598-022-18139-2
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional modulation of evoked synaptic transmission by pulsed infrared light

Abstract: Infrared (IR) neuromodulation (INM) has been demonstrated as a novel modulation modality of neuronal excitability. However, the effects of pulsed IR light on synaptic transmission have not been investigated systematically. In this report, the IR light (2 μm) is used to directly modulate evoked synaptic transmission at the crayfish opener neuromuscular junction. The extracellularly recorded terminal action potentials (tAPs) and evoked excitatory postsynaptic currents (EPSCs) modulated by localized IR light illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…However, it was suggested that Na + channels do not play as significant a role for an IR light block of the CAP propagation. A more recent study [117] also identified an IR light-induced K + channel-mediated potential component in the crayfish motor axons capable of disrupting any rhythmic axonal AP firing. Its amplitude and polarity were dependent on the membrane potential.…”
Section: Current Understanding Of Mechanisms Of Ir Nerve Inhibitionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, it was suggested that Na + channels do not play as significant a role for an IR light block of the CAP propagation. A more recent study [117] also identified an IR light-induced K + channel-mediated potential component in the crayfish motor axons capable of disrupting any rhythmic axonal AP firing. Its amplitude and polarity were dependent on the membrane potential.…”
Section: Current Understanding Of Mechanisms Of Ir Nerve Inhibitionmentioning
confidence: 95%
“…IR light irradiation aimed onto the presynaptic neuronal soma or axon has been shown to enhance the spontaneous inhibitory postsynaptic currents via altering the GABAergic neurotransmission in rat cortical neuron cultures [54]. Moreover, the direct contribution from synapses under pulsed IR light [117] in the case of illuminating neuronal networks should also be incorporated (see section 6.1 below). [29,35,39] and even potentially higher, without inducing histological damage in neurons [44,[118][119][120] or astrocytes [121].…”
Section: Current Understanding Of Mechanisms Of Ir Nerve Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, our understanding of neuronal response is still rudimentary. The underlying mechanism of action is unknown [16][17][18][19][20][21][22][23] and the effect on responses of different neuronal subtypes as well as different physiological states in vivo at a cellular level is still lacking. In particular, even though INS has been shown to induce BOLD activation at distant cortical sites in fMRI studies, little is known about the cellular circuits contributions to this functional connectivity result.…”
Section: Introductionmentioning
confidence: 99%